Anticipation in familial pancreatic cancer. Issue 2 (21st June 2005) - McFaul, C D; Greenhalf, W; Earl, J; Howes, N; Neoptolemos, J P; Kress, R; Sina-Frey, M; Rieder, H; Hahn, S; Bartsch, D K
Abstract : Background: Previous studies of anticipation in familial pancreatic cancer have been small and subject to ascertainment bias. Our aim was to determine evidence for anticipation in a large number of European families. Patients and methods: A total of 1223 individuals at risk from 106 families (264 affected individuals) were investigated. Generation G3 was defined as the latest generation that included any individual aged over 39 years; preceding generations were then defined as G2 and G1. Results: With 80 affected child-parent pairs, the children died a median (interquartile range) of 10 (7, 14) years earlier. The median (interquartile range) age of death from pancreatic cancer was 70 (59, 77), 64 (57, 69), and 49 (44, 56) years for G1, G2, and G3, respectively. These indications of anticipation could be the result of bias. Truncation of Kaplan-Meier analysis to a 60 year period to correct for follow up time bias and a matched test statistic indicated significant anticipation (p = 0.002 and p<0.001). To minimise bias further, an iterative analysis to predict cancer numbers was developed. No single risk category could be applied that accurately predicted cancer cases in every generation. Using three risk categories (low with no pancreatic cancer in earlier generations, high with a single earlier generation, and very high where two preceding generations were affected), incidence was estimated without significant error. Anticipation was independent of smoking. Conclusion: This study provides the first strong evidence for anticipation in familial pancreatic cancer and must be considered in genetic counselling and the commencement of secondary screening for pancreatic cancer.